2018
DOI: 10.31744/einstein_journal/2018ao4322
|View full text |Cite
|
Sign up to set email alerts
|

Nurse work environment: comparison between private and public hospitals

Abstract: Objective To compare the characteristics of the work environment that enable the professional practice of nurses in private and public organizations.Methods A quantitative, exploratory, cross-section study, carried out in four health organizations - one public and three private, with 188 registered nurses. Participants answered the Brazilian version of the Nursing Work Index − Revised, which aims to evaluate the presence of characteristics that favor the development of nursing activities through 15 items distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Values below 2.5 represent favorable environments for the professional nursing practice and, above 2.5, unfavorable environments. In this instrument, the lower the score, the greater the presence of attributes favorable for the professional practice (18,23) . At the international level, the NWI-R, already adapted and validated in several countries, has been applied in several contexts (19,23) .…”
Section: Revised Professional Practice Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Values below 2.5 represent favorable environments for the professional nursing practice and, above 2.5, unfavorable environments. In this instrument, the lower the score, the greater the presence of attributes favorable for the professional practice (18,23) . At the international level, the NWI-R, already adapted and validated in several countries, has been applied in several contexts (19,23) .…”
Section: Revised Professional Practice Environmentmentioning
confidence: 99%
“…In addition, according to some authors, the measures most frequently used to assess work environments were developed more than 20 years ago and, in addition to the lack of robust psychometric tests, there is a limited theoretical component that boosted their development (57) . Consequently, the validity of these instruments can be questioned in terms of their relevance to the current environment of the professional nursing practice (18,57) .…”
Section: Limitations Of the Instruments For Assessing The Environmentmentioning
confidence: 99%
“…However, when using another instrument that evaluates the characteristics of the environment of the professional practice, authors also found more favorable results in private hospitals, when compared to the public ones. (21) With regard to subscales, the Participation of nurses in hospital obtained the most unfavorable evaluation in the perception of the participants and in the evaluation of countries such as the United States of America, China, Thailand, Japan, New Zealand, Germany (22) and Turkey (23) it was possible to perceive that the hospitals surveyed have much to invest in the inclusion of members of the nursing staff in political decisions, commissions and committees, as well as in offering opportunities for professional growth and in a more accessible communication with the managers. (10) In resource adequacy, the second subscale with the most unfavorable evaluation, it was noted that only China and Thailand achieved more favorable results, (22,23) which shows that the feeling of work overload is not present only in the participating professionals of this research.…”
Section: Pes Subscalesmentioning
confidence: 99%
“…[ 8 ] Furthermore, differences in job-related stress between public and private hospitals have been noted. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to a National Health Account's (NHA) report, 70% of Iranian hospitals are in the public sector, whereas private hospitals account for almost 15% of the total number of hospitals. [ 10 ] Studies have shown that environmental differences between public and private hospitals can result in stress among nurses[ 9 11 ] and understanding work place stressors and how these are coped with has attracted interest over recent decades. [ 6 ] Recognizing the importance of assessing the workplace stressors that exist in public and private hospitals and the differences between them, the aim of this study was to examine the perceived occupational stress levels experienced by ICU nurses working in both public and private hospitals in Tabriz, Northwest Iran.…”
Section: Introductionmentioning
confidence: 99%